Autophagy and its role in osteosarcoma - Biao Ning; Yixin Liu; Tianhe Huang; Yongchang Wei (Cancer Medicine, 2023)
Abstract Osteosarcoma (OS) is the most common bone malignancy and preferably occurs in children and adolescents. Despite significant advances in surgery and chemotherapy for OS over the past few years, overall survival rates of OS have reached a bottleneck. Thus, extensive researches aimed at developing new therapeutic targets for OS are urgently needed. Autophagy, a conserved process which allows cells to recycle altered or unused organelles and cellular components, has been proven to play a critical role in multiple biological processes in OS. In this article, we summarized the association between autophagy and proliferation, metastasis, chemotherapy, radiotherapy, and immunotherapy of OS, revealing that autophagy‐related genes and pathways could serve as potential targets for OS therapy.